Secondary school students’ understanding of attributes for solving stoichiometry problems / Norini Jaafar - Jaafar, Norini (Institute of Graduate Studies, UiTM, 2015)
The aim of this study was to offer a comprehensive description of 423 secondary school students’ level of understanding of the three attributes deemed necessary for solving stoichiometry problems. The three attributes were proportional reasoning, mole concept and chemical equation. This study also investigated the students’ ability to solve stoichiometry problems and whether the three attributes have any significant relationship with the ability to solve the stoichiometry problems from the perspectives of academic ability. The students were given an Achievement Test to answer the 19 test items which were divided into three sections of A, B and C and three items for problem solving in Section D. Section A tested the understanding of the proportional reasoning, Section B and C the understanding of the mole concept and the chemical equation respectively. Section D was to determine the ability to solve stoichiometry problems. Cross-sectional descriptive statistics method was employed and the data collected were analysed by frequency counts in terms of percentages…